Peranan Mahasiswa dalam Pengembangan Potensi Desa Wisata dan Kegiatan Tambahan di Jorong Dama Gadang Kabupaten Agam - Tabjung, Lesti; Rino, Rino; Winta, Lasti Rahma; Huda, Syahrul; Istiqomah, Febbi Ari; Adhytia, Fajri (Universitas Negeri Padang, 2024)
Article discusses KKN student activities. KKN activities aim to provide experience and as a learning process for students to explore village potentials that can be developed by the community. The method for implementing KKN at the location consists of survey activities and planning additional activities apart from the core activities that have been planned. Additional KKN student activities receive support from the local government and the Jorong Dama Gadang community. This is shown in many KKN student activities involving people from various groups. The Jorong government and its officials involve many KKN students in carrying out activities such as socialization on Bullying and the Spirit of Learning, teaching activities at schools, and Posyandu activities. Other forms of activities involving young teenagers and elementary school level children include activities at the Qur’an Study Park to accompany and teach the Qur’an, healthy exercise carried out in the community and also in the school environment, keeping the environment clean with community service, and rearranging boundaries. hamlet boundaries. Padang State University KKN activities are expected to provide benefits to the community, especially those aimed at creating peace and developing the potential of tourist villages